Cyr61 as mediator of Src signaling in triple negative breast cancer cells - Sánchez-Bailón, María Pilar (Oncotarget, 2015)
SFKs are involved in tumorigenesis and metastasis. Here we analyzed c-Src contribution to initial steps of metastasis by tetracycline-dependent expression of a specific shRNA-c-Src, which suppressed c-Src mRNA and protein levels in metastatic MDA-MB-231 cells. c-Src suppression did not alter cell proliferation or survival, but it significantly reduced anchorage-independent growth. Concomitantly with diminished tyrosine-phosphorylation/activation of Fak, caveolin-1, paxillin and p130CAS, c-Src depletion also inhibited cellular migration, invasion and transendothelial migration. Quantitative proteomic analyses of the secretome showed that Cyr61 levels, which were detected in the exosomal fraction, were diminished upon shRNA-c-Src expression. In contrast, Cyr61 expression was unaltered inside cells. Cyr61 partially colocalized with cis-Golgi gp74 marker and with exosomal marker CD63, but c-Src depletion did not alter their cellular distribution. In SUM159PT cells, transient c-Src suppression also reduced secreted exosomal Cyr61 levels. Furthermore, conditional expression of a c-Src dominant negative mutant (SrcDN, c-Src-K295M/Y527F) in MDA-MB-231 and in SUM159PT diminished secreted Cyr61 as well. Cyr61 transient suppression in MDA-MB-231 inhibited invasion and transendothelial migration. Finally, in both MDA-MB-231 and SUM159PT, a neutralizing Cyr61 antibody restrained migration. Collectively, these results suggest that c-Src regulates secreted proteins, including the exosomal Cyr61, which are involved in modulating the metastatic potential of triple negative breast cancer cells.